Permanent His-bundle pacing is feasible, safe, and superior to right ventricular pacing in routine clinical practice - Sharma, Parikshit S.; Dandamudi, Gopi; Naperkowski, Angela; Oren, Jess W.; Storm, Randle H.; Ellenbogen, Kenneth A.; Vijayaraman, Pugazhendhi (Heart rhythm, 2015)
Right ventricular pacing (RVP) has been associated with heart failure and increased mortality. His-bundle pacing (HBP) is more physiological but requires a mapping catheter or a backup right ventricular lead and is technically challenging. We sought to assess the feasibility, safety, and clinical outcomes of permanent HBP in an unselected population as compared to RVP. All patients requiring pacemaker implantation routinely underwent attempt at permanent HBP using the Select Secure (model 3830) pacing lead in the year 2011 delivered through a fixed-shaped catheter (C315 HIS) at one hospital and RVP at the second hospital. Patients were followed from implantation, 2 weeks, 2 months, 1 year, and 2 years. Fluoroscopy time (FT), pacing threshold (PTh), complications, heart failure hospitalization, and mortality were compared. HBP was attempted in 94 consecutive patients, while 98 patients underwent RVP. HBP was successful in 75 patients (80%). FT was similar (12.7 ± 8 minutes vs 10 ± 14 minutes; median 9.1 vs 6.4 minutes; P = .14) and PTh was higher in the HBP group than in the RVP group (1.35 ± 0.9 V vs 0.6 ± 0.5 V at 0.5 ms; P < .001) and remained stable over a 2-year follow-up period. In patients with >40% ventricular pacing (>60% of patients), heart failure hospitalization was significantly reduced in the HBP group than in the RVP group (2% vs 15%; P = .02). There was no difference in mortality between the 2 groups (13% in the HBP group vs 18% in the RVP group; P = .45). Permanent HBP without a mapping catheter or a backup right ventricular lead was successfully achieved in 80% of patients. PTh was higher and FT was comparable to those of the RVP group. Clinical outcomes were better in the HBP group than in the RVP group.